Structure of Non-Oscillatory Solutions for Second Order Dynamic Equations on Time Scales - Yong Zhou; Bashir Ahmad; Ahmed Alsaedi (Mathematics, 2019)
In this paper, we make a detailed analysis of the structure of non-oscillatory solutions for second order superlinear and sublinear dynamic equations on time scales. The sufficient and necessary conditions for existence of non-oscillatory solutions are presented.